Effects of mood episodes and comorbid anxiety on neuropsychological impairment in patients with bipolar spectrum disorder - Chih‐Chun Huang; Yun‐Hsuan Chang; Tzu‐Yun Wang; Sheng‐Yu Lee; Shiou‐Lan Chen; Po See Chen; Hsien‐Yuan Lane; Yen Kuang Yang; Ru‐Band Lu (Brain and Behavior, 2020)
Abstract Objectives Cases of patients with bipolar disorder (BD) having neuropsychological impairment have been reported, although inconsistently. The possibility of comorbidity with anxiety disorder (AD) has been suggested. The association between mood episodes and AD comorbidity on neuropsychological performance is unclear and thus was investigated in the current study. Methods All participants were informed about and agreed to participate in this study. Patients with BD were recruited from outpatient and inpatient settings, and healthy controls (HCs) were recruited as a comparison group. Six hundred and twenty‐eight participants (175 HCs and 453 BD—56 BDI and 397 BDII) were studied based on their current mood episode, namely, depressive (BDd), manic/hypomanic (BDm), mixed (BDmix), and euthymic (BDeu), compared with/without AD comorbidity (164 with AD). Results Compared to HCs, all BD groups had significantly more impaired neuropsychological profiles, but the BDeu group was found to have less impairment in memory and executive function than the episodic BD groups. The percentage of AD comorbidity in BDd, BDm, BDmix, and BDeu was 33.9%, 40.3%, 33.0%, and 35.6%, respectively (χ2 = 1.61, p > .05). The results show that AD plays a different role in neuropsychological impairment across various mood episodes in BD. Conclusion Memory impairment and executive dysfunction may be state‐like cognitive phenotypes and are affected by AD comorbidity during mixed and depressive episodes in BD, while sustained attention deficiencies are more like trait markers, regardless of mood episodes, and persist beyond the course of the illness. The AD comorbidity effect on attentional deficit is greater when suffering from a manic episode.